2002
DOI: 10.1093/treephys/22.12.839
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of seasonal air and soil temperatures on photosynthesis in Scots pine trees

Abstract: Seasonal courses of light-saturated rate of net photosynthesis (A360) and stomatal conductance (gs) were examined in detached 1-year-old needles of Scots pine (Pinus sylvestris L.) from early April to mid-November. To evaluate the effects of soil frost and low soil temperatures on gas exchange, the extent and duration of soil frost, as well as the onset of soil warming, were manipulated in the field. During spring, early summer and autumn, the patterns of A360 and gs in needles from the control and warm-soil p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 39 publications
6
49
1
Order By: Relevance
“…In contrast to the behavior of evergreen species from colder climates, where CO 2 fixation rates close to zero were found in winter (Strand et al 2002), our subject species showed a positive CO 2 balance in this season. In a Mediterranean climate, a depression in net photosynthesis was found in Quercus suber in winter, although the major depression occurred in summer (García-Plazaola et al 1997) concomitantly with stomatal closure, due to drought.…”
Section: Compatible Solutescontrasting
confidence: 99%
“…In contrast to the behavior of evergreen species from colder climates, where CO 2 fixation rates close to zero were found in winter (Strand et al 2002), our subject species showed a positive CO 2 balance in this season. In a Mediterranean climate, a depression in net photosynthesis was found in Quercus suber in winter, although the major depression occurred in summer (García-Plazaola et al 1997) concomitantly with stomatal closure, due to drought.…”
Section: Compatible Solutescontrasting
confidence: 99%
“…The parameters of the root water uptake function were calibrated to obtain the best possible fit of the transpiration. To achieve this, the degree of water uptake was profoundly restricted below a soil temperature of ¾8°C, as observed studies by Mellander et al (2004) and Strand et al (2002) on a young Scots pine stand at a nearby site.…”
Section: Model Applicationmentioning
confidence: 99%
“…Western redcedar had higher (P < 0.05) P n rates than yellow-cedar when minimum air temperature was above freezing. Field and laboratory studies have found low, but above freezing, air temperature can limit the photosynthetic process of conifers [31,33,34,44,47].…”
Section: Net Photosynthesismentioning
confidence: 99%